Nonlinear observer to estimate polarization phenomenon in membrane distillation - Khoukhi, Billal; Tadjine, Mohamed; Boucherit, Mohamed Seghir (International journal for simulation and multidisciplinary design optimization, 2015)
This paper presents a bi-dimensional dynamic model of Direct Contact Membrane Desalination (DCMD) process. Most of the MD configuration processes have been modeled as steady-state one-dimensional systems. Stationary two-dimensional MD models have been considered only in very few studies. In this work, a dynamic model of a DCMD process is developed. The model is implemented using Matlab/Simulink environment. Numerical simulations are conducted for different operational parameters at the module inlets such as the feed and permeate temperature or feed and permeate flow rate. The results are compared with experimental data published in the literature. The work presents also a feed forward control that compensates the possible decrease of the temperature gradient by increasing the flow rate. This work also deals with a development of nonlinear observer to estimate temperature polarization inside the membrane. The observer gives a good profile and longitudinal temperature estimations and shows a good prediction of pure water flux production.